Combating online hate speech: The impact of legislation on Twitter - Raphaela Andres; Olga Slivko (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
We analyze the impact of the Network Enforcement Act, the first regulation which aims at restraining hate speech on large social media platforms. Using a difference-in- differences framework, we measure the causal impact of the German law on the prevalence of hateful content on German Twitter. We find evidence of a significant and robust decrease in the intensity and volume of hate speech in tweets tackling sensitive migration-related topics. Importantly, tweets tackling other topics as well as the tweeting style of users are not affected by the regulation, which is in line with its aim. Our results highlight that legislation for combating harmful online content can influence the prevalence of hate speech even in the presence of platform governance mechanisms.
Keywords: H41; J15; K42; L82; L86; 330; Social Networks; User-Generated Content; Hate Speech; Policy Evaluation